The Effect Of Good Corporate Governance Mechanisms And Corporate Social Responsibility Disclosure On Corporate Value - Fakih, Anas; Subiyanto, Bambang; Digdowiseiso , Kumba (CV ODIS, 2023)
This study elucidates the impact of robust corporate governance mechanisms and transparent corporate social responsibility disclosure on the valuation of a company. The data processing in this study employed SPSS 25.0. A total of 70 samples were collected from 14 companies using purposive sampling techniques over a 5-year research period. The results of the hypothesis test successfully demonstrated that Managerial Ownership has a statistically significant and positive impact on the company's value. The ownership of a larger number of shares by management will effectively decrease conflicts within the company. The results of the hypothesis test demonstrate that the Audit Committee has a substantial and favorable impact on the company's value. The audit committee plays a crucial role in overseeing and enhancing the effectiveness of the financial statement process, ensuring integrity and objectivity. This, in turn, leads to improved company performance and increased company value. Also, there is no discernible impact of Corporate Social Responsibility on the value of a company. The company's sole emphasis on profitability and disregard for non-financial aspects such as corporate social responsibility (CSR) results in minimal disclosure.